PSYCHOLOGICAL BASIS OF FORMING A SPORTS COACH'S PROFESSIONAL IMAGE - Kateryna Shkarlatiuk; Viktor Koshyrets; Alla Hubina (Психологічні перспективи)
Purpose. Grounding psychological conditions and ways of forming a professional image based on the disclosure of the structure and image characteristics of a sports coach.